Dielectric characteristics of erythrocytes of patients with ischemic and hemorrhagic stroke during therapeutic hypothermia - Batyuk, Lilia; Kizilova, Natalia; Kocharova, Tetiana (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):301